The contribution of R&D to production efficiency in OECD countries: econometric analysis of industry-level panel data - Margo Liik; Jaan Masso; Kadri Ukrainski (Baltic Journal of Economics, 2014)
While research and development expenditures are considered a key to productivity growth and development, the question remains whether their contribution could depend on the particular countries' and industries' actual development levels and positions in global value chains. In this paper we analyse the relative contribution of R&D to the efficiency (productivity) on the industry and sector level in OECD countries using industry-level panel data and the stochastic frontier production function approach. The results indicate that R&D capital productivity enhancing effect increases with the level of technology; physical capital shows the opposite effect. The distribution of efficiency across industries shows remarkably different variances, reflecting different degrees of competition and the structure of value chains. Among different external factors, the share of labour with tertiary education at the national level showed a strong positive correlation with efficiency, while for other external factors the effect varied across the industries. The findings imply that in the design of R&D policy measures the structure of the industries needs to be considered.
Keywords: O32; O39; 330; efficiency; R&D; SFA; technological change